The use of micro and nano-sized particles in increasing concrete durability. (3rd July 2020) - Akhnoukh, Amin K.
Abstract: The main objective of this research is to increase the concrete durability by reducing deleterious alkali-silica reactivity (ASR) which results in a substantial damage to concrete members due to induced internal stresses. ASR reaction is initiated when the silica content of the aggregate reacts with Alkali Hydroxide in the mix in the presence of relatively high moisture content. The expansive ASR reaction results in the formation of an expansive gel-like material which induces destructive internal stresses within hardened concrete. In this research, micro and nano-sized supplementary cementitious materials (SCMs) are used in producing concrete with potential ASR reactivity. The micro and nano-sized particles resulted in a reduced air content and smaller void ratio of the produced concrete. The reduced concrete voids resulted in a lower permeability; hence, reduced water content, for the produced concrete, which resulted in a substantial reduction in ASR reaction. Results showed that the reduced ASR reaction is directly correlated to the fineness of the incorporated particles. The outcomes of this research will help to maintain the conditions of ASR prone highway construction projects and reduce the maintenance, repair, and replacement budgets required for the highways network.